Communication Contribution of IPNU Organization Gebang Kec. Cirebon District in the Development of Da'wah - Widia Ningsih; Imron Rosyidi; Sherina Prahitaningtyas (Jurnal Indonesia Sosial Teknologi, 2024)
The NU organization among students is IPNU-IPPNU; of course, it has a role in spreading the wings of Islamic da'wah, primarily through the Internet. Its function is to prevent the internet from being filled with content that does not contain education and people who are not responsible, especially people who can mislead the younger generation today. This study aims to analyze the contribution of IPNU organizational communication in Gebang District, Cirebon Regency, in developing da'wah science. The research method used in this study is the qualitative descriptive method. These sources are gathered based on discussion and linked from one piece of information to another. The data collection techniques used in this study were observation, interviews, and research. This data is analyzed, and then conclusions are drawn. Based on the results of the analysis, it was found that IPNU Gebang District plays a role in the development of da'wah in its area, with various activities held, such as monthly and weekly routines. The forms of activity are Narayanan, Yasin, recitation of Al-Barjanji, and general recitation. Other activities supporting the development of da'wah are developing adolescents' interests and talents, such as journalistic training, graphic design, and public speaking.